SISTEM KONTROL ROBOT PEMINDAH BARANG MENGGUNAKAN APLIKASI ANDROID BERBASIS ARDUINO UNO - Asep Saefullah; Dewi Immaniar; Reza Amar Juliansah (CCIT Journal, 2015)
With the development of mobile technology is not only used as a telephone and sms only, but also can be used as a device to control a robot, as well as Android smartphones are already embedded computer features. Robot technology so can be controlled remotely and the desired user. Robot technology is also one that is able to assist the work of humans, such as the draining of human work, as well as having a high risk. Robot function which was made to minimize the risk associated with large heavy physical tasks, positioning an object, and to move goods from one place to another. Therefore designed a robot movers using a servo motor output arm movement, microcontroller as the brain, Bluetooth as a communication medium to send a data or input from the Android application that acts as a device for controlling a robot remotely.